ENTERPRISE ARCHITECTURE PLANNING (EAP) SI/TI MENGGUNAKAN TOGAF ADM PADA DINAS CIPTA KARYA, TATA RUANG DAN KEBERSIHAN KABUPATEN KUBU RAYA - Windi Irmayani (Universitas Bina Sarana Informatika, 2015)
Department of copyrighted work, spatial and hygiene district of Kubu Raya experiencing operational constraints due to budget, facilities and human resources. These problems can be solved with the construction of information systems with the appropriate information technology. The information systems and information technology can reduce operating costs and maximize existing human resources. It is necessary for Enterprise Architecture Planning (EAP) framework using TOGAF ADM describes the detailed planning process constructions Information Systems/Information Technology with eight phases. Phase A is architecture Vision, phase B is Business Architecture, phase C is Information System Architecture (Data and Application), phase D is Technology Architecture, phase E are Opportunities and Solutions, phase F is Migration Planning, phase G is Implementation Governance, and phase H is Architecture Change Management.Keywords: Information System, Information Technology, Enterprise Architecture Planning, TOGAF ADM.